A Comparative Study of Digital Social Movements in Indonesia, Malaysia, and the Philippines - Taufik; Azis, Aswin Ariyanto; Sofwatulmillah, Geizka; Azizah, Heka Faza Nur; Hamil, Jamaie Hj. (Universitas Muhammadiyah Yogyakarta, 2026)
Over the past two decades, the rise of social media has fundamentally transformed patterns of political mobilization,particularly among Millennials and Generation Z in Southeast Asia. Despite growing scholarly attention to digitalactivism, comparative studies examining how social media shapes youth political mobilization across Southeast Asiancountries with distinct political histories remain limited. This article addresses two questions: how do Millennials andGeneration Z in Indonesia, Malaysia, and the Philippines utilize social media as a space for political mobilization, andwhat structural, cultural, and political factors shape distinct forms of digital youth activism across the three countries.Drawing on the connective action framework and a comparative case study design through qualitative literaturereview, this article argues that digital social movements in these three countries constitute an emergent form of politicalagency shaped by authoritarian legacies, oligarchic structures, and platform-specific affordances. The findingsdisclosed that social media has functioned as a space for constructing collective identities that trigger real-worldmobilization, as evidenced by #ReformasiDikorupsi and #TolakOmnibusLaw in Indonesia, the Bersih movement andanti-Lynas campaign in Malaysia, and #BabaeAko in the Philippines. Across all three cases, social media has servedas a critical bridge between digital discourse and real-world collective action.